Correlation between ultrasonographic, hysteroscopic and histopathological findings in patients with abnormal uterine bleeding - Bhatiyani, Binti R.; Dhumale, Shrikant; ., Pandeeswari; Bashani, Dolly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menstrual disorders are common indication for medical visits among women of reproductive age and heavy menstrual bleeding affects up to 30% of women throughout their reproductive lifetime. This study aims at evaluating the different causes and, the clinical presentation of AUB and to compare the role of hysteroscopy, ultrasonography and histopathology in patients with AUB. Methods: 100 women above 45 years of age, presenting with abnormal bleeding per vaginum were evaluated. All patients underwent transvaginal scan to note down the endometrial thickness and to rule out uterine and adnexal pathology. All the patients underwent diagnostic hysteroscopy, followed by a biopsy of the endometrium using a curette. The endometrium was sent to the pathologist. Findings of these diagnostic modalities then correlated. Results: Incidence of AUB was present between the age groups of 45-49 years of age (66%). The commonest presenting complaint in this series was menorrhagia or heavy menstrual bleeding (60%). The finding of thickened endometrium as the most common abnormality on USG (44%) and also on hysteroscopy (45%). As per present study the sensitivity of hysteroscopy is 97.78% and specificity was 34.55%, the negative predictive value of the test is 95%. Conclusions: TVS may be the first line of investigation while evaluating the endometrium in a perimenopausal AUB. It helps to triage the patients into high risk or low risk. Endometrial thickness >4mm as per the present study needs further evaluation. Patients with endometrial thickness less than 4 mm can be reassured. Hysteroscopy is the gold standard in the diagnosis of focal pathology like sub mucous fibroid, polyps or anomalies. Histopathology probably is an indispensable tool specially to rule out premalignant and malignant conditions. Thus, all the modalities instead of being competitive to one another, are complimentary to each other. For complete evaluation of patient with AUB all the three modalities should be used together to come at exact diagnosis.